2020
DOI: 10.3390/foods9070913
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Human Small Intestinal Digestion of Starch Using an In Vitro System Based on a Dialysis Membrane Process

Abstract: This work deepens our understanding of starch digestion and the consequent absorption of hydrolytic products generated in the human small intestine. Gelatinized starch dispersions were digested with α-amylase in an in vitro intestinal digestion system (i-IDS) based on a dialysis membrane process. This study innovates with respect to the existing literature, because it considers the impact of simultaneous digestion and absorption processes occurring during the intestinal digestion of starchy foods and adopts ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 69 publications
(159 reference statements)
0
5
0
Order By: Relevance
“…On the other hand, this study used a universally recognised protocol that simulates in vitro digestion based on human digestion parameters and uses endogenous human enzymes 28 . Furthermore, in vivo models in humans, with proper physiological parameters, are the ideal way to simulate food digestion, but ethically and financially, it is not always feasible 60 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, this study used a universally recognised protocol that simulates in vitro digestion based on human digestion parameters and uses endogenous human enzymes 28 . Furthermore, in vivo models in humans, with proper physiological parameters, are the ideal way to simulate food digestion, but ethically and financially, it is not always feasible 60 .…”
Section: Discussionmentioning
confidence: 99%
“…In the reverse dialysis method, the dialysis bag is filled with intestinal fluid, and the bag is placed in a container with the compound of interest dissolved [92]. One critical factor in this technique is the pore size of the membrane, which is usually under 20 kDa [93][94][95]. From a different perspective, two approaches can be found in the literature regarding this process.…”
Section: Nonbiological Methodsmentioning
confidence: 99%
“…On the other hand, it is also possible to find some standardized and complex systems for BC prediction for both drugs and foods, such as the TNO Gastrointestinal Model (TIM) or Engineered Stomach and Small Intestine (ESIN), which include dialysis membranes as a last digestion step for simulating intestinal absorption, namely passive absorption [12,97]. For example, González et al, 2020 [95] reported an improved dialysis system based on a continuous flow of fluid at a controlled temperature for a more realistic dynamic small intestine simulation. In 2007, another dialysis system arose: the AMI system.…”
Section: Nonbiological Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A limited number of in vitro researches can be identified to mimic the absorption process by using a semipermeable membrane that allows the passage of digested products (i.e., small molecules) and blocks undigested substrates. [8][9][10] For in vitro systems, it is difficult to implement complex geometrical features of a real small intestine, such as circular folds and villi, which affect the flow pattern and thus the mass transfer. 11,12 Even if some research groups used excised animal intestinal tissues 13 or cultured epithelial cell monolayer, 14 various movements of the intestinal walls, for example, segmentation and peristalsis, can hardly be implemented in those experiments.…”
Section: Introductionmentioning
confidence: 99%